Problematika Guru dalam Melaksanakan Sistem Pembelajaran Kurikulum Merdeka Belajar di SD Takhassus Al-Qur`An Wonosobo - Yeslin Tania Putri; Nasokah Nasokah; Chairani Astina (Khazanah : Journal of Islamic Studies, 2025)
The implementation of the Merdeka Learning Curriculum is a national policy that requires teachers’ readiness to plan, implement, and evaluate learning in a more flexible and student-centered manner. In the context of Islamic-based elementary schools, the implementation of the Merdeka Curriculum also demands teachers’ ability to integrate Qur’anic values into the learning process without eliminating the institution’s distinctive characteristics and identity. This study focuses on the issues surrounding the implementation of the Merdeka Learning Curriculum at SD Takhassus Al-Qur’an Wonosobo. The research problems are formulated as follows: (1) how the Merdeka Learning Curriculum is implemented at SD Takhassus Al-Qur’an Wonosobo, (2) what problematics are faced by teachers in implementing the Merdeka Learning Curriculum, and (3) what efforts are made by teachers to overcome these problematics. This study employs a qualitative approach with a field research design. The research subjects consist of the school principal and teachers of SD Takhassus Al-Qur’an Wonosobo. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results of the study indicate that the implementation of the Merdeka Learning Curriculum at SD Takhassus Al-Qur’an Wonosobo has been carried out gradually in accordance with national policies by applying student-centered learning, learning flexibility, and character strengthening through the integration of Qur’anic values. However, several problematics remain, including teachers’ limited understanding of the Merdeka Curriculum, difficulties in preparing instructional planning documents, challenges in implementing differentiated learning, administrative workload, and the suboptimal use of formative assessment. To address these problematics, teachers have undertaken various efforts, such as improving professional competence through training and self-directed learning, collaborating in the preparation of instructional documents, simplifying administrative tasks, strengthening formative assessment, and integrating Qur’anic values into the learning process. Overall, the implementation of the Merdeka Learning Curriculum at SD Takhassus Al-Qur’an Wonosobo has not yet been fully optimal, but it has been moving in the right direction with the active role of teachers as the main implementers of the curriculum.